LEXICAL AMBIGUITY IN READING ANALYTICAL EXPOSITION TEXTS FOR SENIOR HIGH SCHOOL STUDENTS - Putri Sembiring and Sortha Silitonga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
The objectives of this study were to find out the types of lexical ambiguity and the most dominant type of lexical ambiguity used in analytical exposition texts in English Today 2 and Advanced Learning English 2 textbooks. This study was conducted by using descriptive qualitative method. The research was mainly focused on the four types of lexical ambiguity proposed by Saeed, such as homonymy, polysemy, synonymy and antonymy. In carrying out this study, the data were taken from analytical exposition texts in reading materials and exercise material from the two English textbooks which contained of ambiguous words. The result of the study indicated the numbers of lexical ambiguity were 46 words within homonymy (34,8%), polysemy (28,2%), synonymy (19,6%), and antonymy (17,4%).